Recycling of IRAP from the plasma membrane back to the insulin-responsive compartment requires the Q-SNARE syntaxin 6 but not the GGA clathrin adaptors - Watson, Robert T. (J Cell Sci, 2008)
Insulin recruits two transmembrane proteins, GLUT4 and IRAP, to the plasma membrane of muscle cells and adipocytes. The subcellular trafficking and localization of GLUT4, and to a lesser extent IRAP, have been intensely studied, yet the molecular mechanisms responsible for their insulin-responsive compartmentalization remain unknown. Herein we have investigated the endocytosis and recycling of IRAP from the cell surface back to the insulin-responsive compartment (IRC). Our results show that a key dileucine motif at position 76,77 (LL(76,77)), although required for the initial biosynthetic entry of IRAP into the IRC, is dispensable for entry into the IRC via the endosomal system. Indeed, we found that an AA(76,77) mutant of IRAP is fully capable of undergoing endocytosis and is correctly routed back to the IRC. To verify that the AA(76,77) mutant enters the bona fide IRC, we show that the internalized IRAP-AA(76,77) construct is sequestered in an IRC that is insensitive to brefeldin A yet sensitive to a dominant-interfering mutant of AS160 (AS160-4P). In addition, we show that the GGA clathrin adaptors are not required for the re-entry of IRAP from the cell surface back into the IRC, whereas the Q-SNARE syntaxin 6 is required for this process.